Proof in civil and arbitration process and modernization of judicial system of Russia - V V Grebennikov; L YU Grudtsina (RUDN Journal of Law, 2015)
In article a valid conclusion that the direction of creative activity of court (including, in aspect of a judicial discretion regarding proof and an assessment of evidentiary base) deserves to be a program question of extraordinary congress of judges of Russia to define one of many constant purposes of activity of all judicial system. To have opportunities to modernize, bring new and positive in a condition of modern judicial system, carriers of judicial authority need to find modern knowledge, to be exempted from the outdate, become obsolete representations, to penetrate into the latest tools, means of legal proceedings more deeply, to learn possibilities of the personality as judges - the carrier of judicial authority and to be capable to apply them to updating of establishments of judicial system in daily judicial activity.